Apostolo Zeno: Poesie drammatiche, Parte I, Volume 1: Parte I: Venezia e oltre Vol. 1: da Gl'Inganni felici (1696) a Temistocle (1701) - Noe, Alfred (2021)
This is the first part of a critical edition of the complete dramatic works by Apostolo Zeno. Vol. I.1 offers 10 librettos: Gl'Inganni felici, Il Tirsi, Il Narciso, I rivali generosi, Eumene, Odoardo, Faramondo, Lucio Vero, Griselda, Temistocle. Parte I Volume 1: https://e-book.fwf.ac.at/o:1587 Parte I Volume 2: https://e-book.fwf.ac.at/o:1588